Efforts to Improve Student Learning Outcomes in Grade VIII Middle School on Flat Sided Building Materials Through The Power of Two Learning Strategy - Kristina, Yevin (Asian Journal of Applied Education (AJAE), 2023)
This study aims to improve students' mathematics learning outcomes by using the cooperative learning model of The Power of Two type. Based on these objectives, this research uses Classroom Action Research (CAR). This research was conducted at SMPN 31 Medan which is located at Jl. Jamin Ginting Km.13, Lau Cih, Kec.Medan Tuntungan, Medan City, North Sumatra 20137. The cycle in this study consisted of four steps, namely planning (plan), action (action), observation (observation), and reflection (reflection). . The steps in the next cycle are planning that has been revised, action, observation, and reflection. Before entering the cycle, I take preliminary action in the form of problem assistance. Student learning outcomes have increased through the application of the Cooperative learning model type power of two, this is obtained based on student learning outcomes tests that have been carried out in the initial test, cycle I to cycle II. In the first learning outcomes test in cycle I with an average student learning completeness increased to 76.1 (enough category). Up to the second cycle II learning outcomes test with an average student learning completeness of 87.7 (high category).